1998
DOI: 10.1111/j.1346-8138.1998.tb02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Generalized Morphea with Histological Changes in Lichen Sclerosus et Atrophicus and Lichen Planus

Abstract: We reported a 44-year-old Japanese woman with generalized multiple sclerotic plaques, which showed histological findings of morphea. This patient also had an erosive lesion on her mouth; its histological findings were consistent with lichen planus. A sclerotic lesion on her thigh showed the histological findings of lichen sclerosus et atrophicus (LSA). These data suggest that similar etiologic events or closely related pathologic processes are involved in morphea, lichen planus, and LSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 3 publications
0
20
1
4
Order By: Relevance
“…Morphea and LSA coexisting in the same biopsy specimen has also been described 10 . With sequential biopsies, several investigators have reported transition from LSA to morphea or vice versa 10,11 . However, other investigators believe there are enough clinical and histologic differences between LSA and morphea to argue that they are distict diseases and that coexistent lesions are coincidental 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphea and LSA coexisting in the same biopsy specimen has also been described 10 . With sequential biopsies, several investigators have reported transition from LSA to morphea or vice versa 10,11 . However, other investigators believe there are enough clinical and histologic differences between LSA and morphea to argue that they are distict diseases and that coexistent lesions are coincidental 1 .…”
Section: Discussionmentioning
confidence: 99%
“…So, the histopathological findings are crucial for making the differential diagnosis between LSA and morphea. Many authors have described coexistent LSA and morphea 9,10 . Morphea and LSA coexisting in the same biopsy specimen has also been described 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Des similitudes entre lichen scléreux, lichen plan et morphées existent. Ces affections peuvent d'ailleurs être associées [17][18][19][20][21][22][23][24][25], suggérant des mécanismes étiopathogéniques communs. Si divers facteurs ont été évoqués, l'étiologie du LS reste inconnue et probablement multifactorielle.…”
Section: Discussionunclassified
“…The coexistence of diseases with an autoimmune pathogenesis, such as morphea, lichen sclerosus, lichen planus and lupus erythematosus are well-known [35,36,37]. Patients with preexisting scleroderma are at increased risk of experiencing a worsening of their condition after radiotherapy, as are patients with other conditions from the spectrum of autoimmune diseases [15].…”
Section: Discussionmentioning
confidence: 99%